Characteristics of European inland ports: A statistical analysis of inland waterway port development in Dutch municipalities. (August 2015) - Wiegmans, Bart; Witte, Patrick; Spit, Tejo
Graphical abstract: The relation between inland waterway terminal, inland port and municipality. Highlights: Presence of a container terminal is important for inland ports' volume and growth. Freight type diversity influences cargo throughput. Inland port regional road network accessibility is important for ensuring cargo throughput. Investments in inland port activities do not lead to employment growth. Cargo throughput level of inland ports is inversely related to growth in throughput. Abstract: Most scientific attention in port studies centers on deep-sea ports, in particular container ports. In our paper, in contrast, we focus our attention on the characteristics of inland waterway ports in a European context. This is an overlooked part in the scientific literature on inland port development, which is up to now mainly concerned with US-based understandings of inland ports. We try to broaden the application of the inland port concept by explaining the development of inland ports in terms of inland waterway bounded cargo throughput. Based on a large-scale quantitative dataset of inland port development in Dutch municipalities we perform various statistical analyses to arrive at a more detailed understanding of the question: What are the characteristics of European inland waterway ports and what transport and economic factors influence cargo throughput on the municipal level? The results in particular highlight the importance of the presence of a container terminal, the diversity in types of goods which are being handled by the inland port and the accessibility of the inland port relative to the regional motorway network as important factors in explaining the size and growth of inland ports. Interestingly, the popular claim in policy of 'investments in inland port development leading to employment growth' cannot be confirmed.